PERKEMBANGAN ‘ILM AL-ṢARF DALAM LEKSIKOLOGI ARAB - Ni'mah, Umi Nurun (Adabiyyāt: Jurnal Bahasa dan Sastra, 2019)
This paper seeks to discover the relationship between the development of ‘ilm al-ṣarf and of the Arabic lexicography. The analysis is made based on the entries of the Arabic dictionaries—which are the samples of this research. The dictionaries taken as the samples are those produced between the second century (first generation) and the twentieth century of Hijriya. The three concepts of ‘ilm al-ṣarf— tajrīd, i’lāl, and binā—are applied to analyse them. This article aims to trace and elucidate the development of the three concepts as they appear in the dictionaries. Based on the analysis, it is found that ilm al-ṣarf has evolved through time even though its basic principles had been applied from the first edition of the Arabic dictionaries.